1999
DOI: 10.1093/fampra/16.4.343
|View full text |Cite
|
Sign up to set email alerts
|

Women battering in primary care practice

Abstract: The purpose of this article is to describe the prevalence of intimate partner violence in primary care populations and review the known physical, mental health and pregnancy consequences of abuse as well as discuss the implications of intimate partner violence on primary care practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
44
1
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 63 publications
1
44
1
2
Order By: Relevance
“…3,7,8 All the fi ndings regarding prevalence of intimate partner violence are compatible with those from international studies on primary health care services. 5,7,[13][14][15] The prevalence of physical and sexual violence in this study were, however, higher than those from other Brazilian studies. 10,19 This may have been because of differences in how the questionnaire was applied, thereby resulting in greater revelation, or because of the samples' size.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…3,7,8 All the fi ndings regarding prevalence of intimate partner violence are compatible with those from international studies on primary health care services. 5,7,[13][14][15] The prevalence of physical and sexual violence in this study were, however, higher than those from other Brazilian studies. 10,19 This may have been because of differences in how the questionnaire was applied, thereby resulting in greater revelation, or because of the samples' size.…”
Section: Discussionmentioning
confidence: 69%
“…Studies carried out in health services 5,[13][14][15] have presented even higher rates, ranging from 20% to 50% for lifetime physical and/or sexual violence by an intimate partner. They have also indicated that 12% to 25% of primary care users report violence by their partner in the previous year, as 4% to 17% of prenatal service users and 12% to 22% of emergency service users.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Lack of offi ce protocols and limited time are perceived as common barriers by medical clinicians. [5][6][7][8] In one study, battered women perceived clinician reluctance to ask about abuse as a major barrier to their domestic violence disclosure.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Among clinical populations, IPV prevalence rates among female patients is 15% to 55%. [8][9][10][11][12][13][14][15][16][17][18][19] It is also recognized as contributing to a wide spectrum of women's health issues, including chronic pain syndromes, gastrointestinal disorders, depression, anxiety, and substance use. 12,[20][21][22][23][24][25][26] A longer experience with IPV is associated with incrementally worse health outcomes for women.…”
mentioning
confidence: 99%